Investigation On The Impedance Modeling Of Combination Circle For Frequency Selective Surface (FSS) - Md Fauzi, Noor Azamiah; Abd Aziz, Mohamad Zoinol Abidin; Meor Said, Maizatul Alice; Othman , Mohd Azlishah; Ahmad, Badrul Hisham; Sulaiman, Hamzah Asyrani; Suaidi, Mohamad Kadim; Mohd Fareq, Abd Malek (Asian Research Publishing Network (ARPN), 2015)

(untitled)
This paper presents the investigation of a unit cell for combination of circle frequency selective surface (FSS). Two types of configuration for the simulation has been investigated and analyzed. The investigation has been done on the radius of circle FSS (a) and the spacing between the first and another circle (b) in order to analyze its effects towards the resistance and reactance of the circuit. The impedance mathematical modeling of the design FSS in terms of, resistance and reactance have been formulated from parameters a, b, c and d. This model can be used to design the FSS at the ISM band application. The bandwidth of the first configuration is 158.27 MHz which covered the frequency range from 2.3261 GHz until 2.4843 GHz. Meanwhile, the bandwidth for the second configuration is 297.17 MHz which covered the frequency range from 2.1515 GHz until 2.4486 GHz.